Ag modification of SBA-15 and MCM-41 mesoporous materials as sorbents of thiophene. (1st March 2022) - Liu, Yang; Liao, Junjie; Chang, Liping; Bao, Weiren
Graphical abstract: Highlights: The adsorption of sorbent for thiophene was accompanied by S-Ag and π complexation. Ag-O-Si is the main active center for adsorption of thiophenic compounds. Charge density of sulfur atom affects S-Ag bond between thiophenic compounds and Ag. Abstract: Zeolites and some mesoporous materials modified by Ag possess excellent desulfurization performances toward the adsorption of thiophenic compounds. However, Ag in Ag-based sorbents has different forms, and the interactions between different forms of silver and thiophene still require further studies. In this paper, pure silica SBA-15 and MCM-41 mesoporous materials with weak acidity were loaded with Ag from the silver ammonia solution to form Ag/SBA-15 and Ag/MCM-41 sorbents. By comparing the desulfurization efficiencies of the sorbents in the simulated solution of thiophene-cyclohexane, thiophene-benzene, tetrahydrothiophene-cyclohexane and tetrahydrothiophene-benzene, it is found that the adsorption of sorbent for thiophene was accompanied by S-Ag and π complexation, and the adsorption performances of thiophene by the sorbents were greatly affected by benzene. The XPS results show that most Ag in Ag/SBA-15 and Ag/MCM-41 sorbents was metallic Ag, and some Ag strongly interacting with the carrier led to the formation of Ag-O-Si bonds as the main active center of thiophenic compounds. In addition, the sulfur atomic mulliken charges (e - ) of different thiopheic compounds (thiophene, tetrahydrothiophene, methylthiophene) will affect the interactions between active components Ag and thiophene sulfur compounds. The desulfurization efficiencies of the sorbents in thiophene-cyclohexane, 2-methylthiophene-cyclohexane, and 3-methylthiophene-cyclohexane showed that the decrease in mulliken charges (e - ) of sulfur atoms facilitated the S-Ag bond interaction between the sulfur atom of thiophenic compounds and active component in the sorbent. In conclusion, to obtain the Ag-based sorbent with good adsorption performance for thiophenic compounds, the carrier should contain a certain content of silicon hydroxyl and the suitable pore structure. During the preparation of SBA-15 and MCM-41 mesoporous materials modified by Ag, the Ag-O-Si bonds are more easily formed when silver ammonia interacts with the silicon hydroxyl group on the surface of the carrier. The suitable pore size can inhibit agglomerate to form metallic Ag during the calcination process. These conclusions will provide theoretical guidance for the preparation of silver-based sorbents for thiophene.